Effects of Deep Breathing Relaxation Techniques and Hand Movements on Elderly Fitness - Damayanti, Alifiana Agma Putri; Mujito, Mujito; Mulyadi, Arif; Myint, Nyein Moh Moh (Health Gate, 2025)
Older adults are individuals aged over 60 years who experience the aging process, which is accompanied by various physical, psychological, and social changes. One of the essential aspects of aging is physical fitness, which refers to the body’s capacity or endurance to carry out daily activities. The Kogerta deep breathing relaxation technique is considered a relevant non-pharmacological intervention to improve the physical fitness of older adults. This study aimed to evaluate the effectiveness of the Kogerta deep breathing relaxation technique on the physical fitness of elderly individuals.This research employed a pre-experimental design and was conducted at the UPT Pelayanan Sosial Tresna Wredha Blitar in Tulungagung. The population consisted of 77 older adults, from which a sample of 20 participants was selected using purposive sampling. The results showed a decrease in the mean pulse rate from 90.10 to 75.65 beats per minute, and an increase in the mean walking distance from 437.50 to 526.50 meters after the intervention. Statistical analysis revealed a significant effect of the Kogerta deep breathing relaxation technique on physical fitness, with a p-value of .001 (p < .05).These findings suggest that the technique has a positive effect on the physical fitness of older adults. The integration of this relaxation technique into elderly care programs has the potential to enhance the overall quality of life among the aging population. Keywords: older adults, Kogerta deep breathing relaxation, physical fitness